A New Progressive Method for Solving Unit Commitment - Kaundinya, N.V.; Prakash, Ch.Das (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
As the electric sector modernizes every time many of the modern algorithms for controlling the generating units need modification. The modern unit commitment problems mainly focus to reduce the operation costs. The Generation companies operate their generators with an aim to maximize their own profit to match the competition in the market. In such scenario price plays a major role in decision process. Here we introduce new technique called imperialistic competition algorithm (ICA) to solve the unit commitment (UC) problem. The method presented in this paper helps the electrical companies to make decision in how to schedule generators to gain more profit. Applying this new algorithm to systems of 10 generating unit will depicts the performance of the algorithm.